A STUDY ON EFL TEACHERS’ OWN CRITERIA IN SELECTING ENGLISH TEXTBOOK FOR SECONDARY SCHOOL STUDENTS IN TERNATE CONTEXT - Samsudin Hi Adam; Silvani Umar Ali (FKIP Universitas Khairun, 2020)
Selecting an ideal textbook is challenging and thoughtful task for most teachers especially at the time when many textbooks are available in bookstores. Selecting a suitable textbook becomes a critical issue since it can have enormous impact on students’ engagement, motivation to learn, and ultimately their language performance. Many criteria should be considered by the teachers in order to reach students’ positive learning outcome. This study aimed to investigate teachers’ own criteria in selecting English textbook for secondary schools students in Ternate, North Maluku context. The participants of this study were 30 English teachers (20 females, 10 males) at state senior secondary schools in Ternate context. The chosen participants were those who have more than three years teaching experiences. The data were collected by using a set of questionnaire and semi- constructed interview. The findings show that most of English teachers’ criteria are matching to latest curriculum, covering four skills, and containing a lot of activities.